Asymmetric returns : - Ineichen, Alexander M (Wiley, 2007)
In Asymmetric Returns, financial expert Alexander Ineichen elevates the critical discussion about alpha versus beta and absolute returns versus relative returns. He argues that controlling downside volatility is a key element in asset management if sustainable positive compounding of capital and financial survival are major objectives